A expansão da graduação na Universidade Federal de São Paulo no período de 2003 a 2012 - Rossetto, Maria Bernadete de Noronha Dantas [UNIFESP] (2017)
The expansion of the Federal Institutions of Higher Education (Instituições Federais de Ensino Superior – IFES) in Brazil was an important process for higher education in the country, especially in the last two decades, and counted on the Program for the Expansion of Brazilian Universities (Programa de Expansão das Universidades Brasileiras) and the Program for Support to Restructuring Plans and Expansion of Federal Universities (Programa de Apoio a Planos de Reestruturação e Expansão das Universidades Federais – REUNI). The Federal University of São Paulo (Universidade Federal de São Paulo – UNIFESP) has followed this national process, with specificities and great transformation. This research aimed to analyze the process of graduation expansion in the institution, between 2003 and 2012. Its description was made from its adhesion to the national process until the end of the REUNI program, as well as its analysis in relation to the national expansion of the IFES in the period. It was decided to carry out a case study, with a descriptive-analytical methodology and documentary analysis. The collected data were analyzed through the technique of content analysis and thematic modality. The analysis, properly speaking, came about through in-depth reading of the documents and identification of 132 Contextual Units (UC). 341 Registration Units (UR) were identified of the UC, from which emerged categories and subcategories. The documents included in this research were official publications (12 documents), legislations (4), institution’s management publications and Meeting Minutes of the University Council of UNIFESP, between 2003 and 2012 (141). The documents showed that the general panorama of higher education, in the first phase of the expansion (2003 to 2007) was a crisis in Brazil's higher education and pointed to the recognition of the strategic role of public higher education and the need for a reform of higher education. In the period between 2008 and 2012, the documents reinforced the panorama already outlined, the need to articulate the axes of expansion and the more precise definition of goals. There was an overall growth of IFES in the expansion process as a whole (first phase and REUNI program) of 106% in the number of campuses (from 148 to 305) and 125% in the number of courses (from 2078 to 4,672). The process of graduation expansion at UNIFESP started, effectively, in 2004. From the quantitative data of the analyzed documents, it was observed that the percentage increase of 500% in the number of campuses, 834% in the number of places for admission and 980% in the number of courses. In addition to this quantitative increase, UNIFESP also diversified its area of activity with the inclusion of human, social, applied and exact science courses. The expansion process at the Federal University of São Paulo, between 2003 and 2012, can be considered as unique among the IFES in Brazil, in relation to what happened in the federal public higher education in the country. Its uniqueness is due both to the transformative potential of this expansion and to the growth in the number of campuses, undergraduate courses and enrollments, in relation to national parameters. We observed the transformative character that the expansion brought to UNIFESP, which, from a university in the area of health, became a full university.